SEM and EDX Study of Zinc-Magnesium Phosphate Coatings on Mild Steel Surfaces - Fachikova, Dimka I.; Liubenova, Tsvetelina L. (Archives of Metallurgy and Materials, 2026)
The work presents results of the formation, composition, structure and corrosion resistance of phosphate coatings on mild steel surfaces, obtained in zinc-magnesium phosphating solutions. The mass/thickness of the coating has been measured by means of gravimetric technique under the following conditions: concentration of the working solutions 5, 10, 15 and 20 vol.%; duration of the process 5, 10, 15 and 20 min; temperature 20, 40, 60 and 80°C. The elements that make up the coatings are determined by EDX analysis. The morphology and topography of the coatings are investigated by scanning electron microscopy (SEM). Potentiodynamic polarization measurement was used to determine the corrosion resistance and protective ability of the coatings.